COST MANAGEMENT AND EXPENSE CONTROL IN COMMERCIAL COMPANIES - Pashakhodzhayeva Dzhamilya Dzhabbarkhanovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
• Ai Rohimah, Purwanti, A. Manajemen, Pengendalian Biaya, Efisiensi Operasional, Keputusan Strategis (2025). Analisis Peran Akuntansi Manajemen Dalam Pengendalian Biaya. https://www.semanticscholar.org/paper/14ce04055fe4756c2c688d5cbda4c4e20310e374 • Marjorie Katherine Crespo García, Juan Carlos Muñoz Briones, Jonathan Alexander Ruiz Carrillo, Benicio Acosta Enriquez (2024). Cost Management: Cost Approach as a Management Tool. https://digrafica.net/catalogo/ • Boutiette, James P. (1958). Management considerations in the control of factory expense. https://open.bu.edu/bitstream/2144/6416/1/Boutiette_James_1958_web.pdf • Dr Perelayefa George Owota, Dr Confidence Joel Ihenyen, James Alabor Odoni (2025). Financial Fitness for Small Businesses in Bayelsa State: Role of Cost Management Strategies in Driving Revenue Growth. https://www.iiardjournals.org/get/JPASWR/VOL.%2010%20NO.%205%202025/FINANCIAL%20FITNESS%20FOR%20SMALL%206-18.pdf • Maci, Martin Matejicek, Lukas Peter, F. Lefley, Petra Maresova (2024). Medical device regulation and its impact on the industry: A case study of Czech companies. https://www.semanticscholar.org/paper/eb5ccb4800f8902aa772591daa17d066349e6e94 • Christian Zwerenz (2019). Exploring Corporate Compliance - New Perspectives on how Companies Deal with Regulatory Requirements.. https://doi.org/10.46289/busf4856 • Asih Nur’aidah, Nadya Ayu Puspita, Nisya Z Nurwulan Sari, Rachmat Agus Santoso (2024). ANALISIS PENYUSUNAN ANGGARAN BIAYA OPERASIONAL CV. SUKSES BERSAMA. https://doi.org/10.34005/akrual.v5i2.3625 • Aguh Patrick. S., Dr. Nwosu Moses. C., Ezeanyim, Okechukwu C. (2020). Multidimensional Budgeting Concepts and Budget Control Modeling For Production Systems Performance Efficiency. https://core.ac.uk/download/552532109.pdf • Endah Susilowati (2023). Cost Management and Strategic Decision Making: The Role of Managerial Accounting. https://www.semanticscholar.org/paper/270cea4f3757dd601118eaf3566586afb56d2b88 • Goloshchapova, Elena I. Zatsarinnaya, Aishat A. Akhmadova (2025). ANALYSIS OF THE APPLICATION OF COST ACCOUNTING IN FINANCIAL MANAGEMENT OF AN ENTERPRISE. https://www.semanticscholar.org/paper/7fd3338aa258aee28d7dfc08a6ddca9f6efd16df • Samuel A. Adai, Murtadho M. Alao (2022). Cost Management as a Panacea for Profitability in Organizations. https://www.asiapacificjournals.org/media/media/article/crc/IJTIM-2021-02-03-10.pdf • Rafinda, Afiq Chamim Mubaroq, Putri Purwaningtyas, Hasan Aljafa, Christian Rotimi Barika (2025). Sustainable Financial Management for Hospitals: A Conceptual Framework. https://www.semanticscholar.org/paper/38bbf4e8b5c05feeca3f240c702bc8908826dcad • Stefan Milojević, Snežana Knežević, Malči Grivec, Olivera Đokić (2024). Cost Management of Healthcare Organizations for Financial Sustainability. https://www.semanticscholar.org/paper/7d2374a8863881a87319a3e3472d3ddea5ee2c55 • Samar S. Alharbi (2024). Gear Up for Development: The Automation Advantage for Sustainability in Manufacturing in the Kingdom of Saudi Arabia. https://www.semanticscholar.org/paper/7c263f0908ee432cb8ab7e869adca62113adb88a • Adeyemo Abidemi (2024). The Role of Technology and Automation in Streamlining Business Processes and Productivity for SMEs. https://www.semanticscholar.org/paper/0aef8b09499b3099848ca1218f5be8a803a23b30